2019
DOI: 10.1021/jacs.8b10930
|View full text |Cite
|
Sign up to set email alerts
|

Mild Covalent Functionalization of Transition Metal Dichalcogenides with Maleimides: A “Click” Reaction for 2H-MoS2 and WS2

Abstract: The physical properties of ultrathin transition metal dichalcogenides (2D-TMDCs) make them promising candidates as active nanomaterials for catalysis, optoelectronics, and biomedical applications. Chemical modification of TMDCs is expected to be key in modifying/adding new functions that will help make such promise a reality. We present a mild method for the modification of the basal planes of 2H-MoS2 and WS2. We exploit the soft nucleophilicity of sulfur to react it with maleimide derivatives, achieving coval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 43 publications
6
94
0
Order By: Relevance
“…Few‐layers MoS 2 colloids were obtained through LPE in N ‐methyl‐2‐pyrrolidone, NMP, using an ultrasonic probe. In this case, we resorted to NMP instead of 2‐propanol ( i PrOH)‐water mixtures to increase the concentration of the colloids and facilitate characterization. Exfoliated MoS 2 was separated from non‐exfoliated material using centrifugation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few‐layers MoS 2 colloids were obtained through LPE in N ‐methyl‐2‐pyrrolidone, NMP, using an ultrasonic probe. In this case, we resorted to NMP instead of 2‐propanol ( i PrOH)‐water mixtures to increase the concentration of the colloids and facilitate characterization. Exfoliated MoS 2 was separated from non‐exfoliated material using centrifugation.…”
Section: Resultsmentioning
confidence: 99%
“…The second weight loss is much more pronounced in the functionalized material compared to the pristine MoS 2 . ATR‐FTIR of the functionalized sample (Figure c) showed conclusive evidence of functionalization, including the presence of the main vibrational modes of Bn‐mal, like the carbonyl stretch (1694 cm −1 ), and the disappearance of the alkene C−H bending mode (840 cm −1 in Bn‐mal), and the emergence of a S‐C stretching mode (728 cm −1 ) that confirms the covalent functionalization of the material through a new S‐C covalent bond . X‐ray photoemission spectroscopy (XPS) further confirmed the covalent attachment of the organic polymer (Figure d–g, Figure S11–S12, Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peréz et al. reported the covalent functionalization of semiconducting MoS 2 and WS 2 by taking advantage of the reaction between soft, nucleophilic sulfur atoms and soft, electrophilic maleimides at room temperature through a Michael‐type addition reaction (Figure b) . The chemical modification of the dichalcogenide materials was investigated by attenuated total reflectance IR spectroscopy, cross‐polarization magic angle spinning (CP‐MAS) 13 C NMR, XPS, and high‐resolution TEM.…”
Section: Exfoliation Approachesmentioning
confidence: 99%
“…In particular, covalent modification of TMDs refers to a reductive functionalization of nanosheets with electrophiles and involves the formation of a new carbon-chalcogen bond. 107 The pioneering work in this direction was published by Voiry et al, who exploited the reaction between ce-1T-MoS2, WS2 and MoSe2 with alkyl halides and aryl diazonium salts, leading to dramatic changes in the optoelectronic properties of the involved TMD nanosheets. 108 More specifically, the authors reported on the reaction through which the electrophile species attack the negatively charged nanosheets and a new carbonchalcogen bond is formed, with a degree of functionalization around 20%.…”
Section: Covalentmentioning
confidence: 99%